Interassociation consensus recommendations for pitch-side emergency care and personal protective equipment for elite sport during the COVID-19 pandemic - Hodgson, L.; Phillips, G.; Gordon, J.; Hanson, J.; Maclean, J.; Mathema, P.; Smith, A.; Woolcock, M.; Cowie, C. M.; Kemp, S.; Patterson, M.; Larkin, J.; et al. (British Journal of Sports Medicine, 2021)
The COVID-19 pandemic has necessitated many novel responses in healthcare including sport and exercise medicine. The cessation of elite sport almost globally has had significant economic implications and resulted in pressure to resume sport in very controlled conditions. This includes protecting pitch-side medical staff and players from infection. The ongoing prevalence of SARS-CoV-2 and the desire to resume professional sport required urgent best practice guidelines to be developed so that sport could be resumed as safely as possible. This set of best practice recommendations assembles early evidence for managing SARS-CoV-2 and integrates expert opinion to provide a uniform and pragmatic approach to enhance on-field and pitch-side safety for the clinician and player. The nature of SARS-CoV-2 transmission creates new hazards during resuscitation and emergency care and procedures. Recommendations for the use and type of personal protective equipment during on-field or pitch-side emergency medical care is provided based on the clinical scenario and projected risk of viral transmission.